2004
DOI: 10.1038/labinvest.3700161
|View full text |Cite
|
Sign up to set email alerts
|

AL-amyloidosis and light-chain deposition disease light chains induce divergent phenotypic transformations of human mesangial cells

Abstract: Human mesangial cells (HMCs) are injured by either excessive amounts or abnormal light chains (LCs), or a combination of both in patients with plasma cell dyscrasias. Consequently, these HMCs undergo phenotypic transformations. HMCs were incubated with eight different light-chains (LCs) for 96 h. These cells, in addition to 51 patient samples from patients with AL-amyloidosis (AL-Am), light-chain deposition disease (LCDD), myeloma cast nephropathy (MCN) and controls were analyzed by immunohistochemistry for CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 38 publications
5
95
0
2
Order By: Relevance
“…In animal studies, the type of kidney disease is dictated by the monoclonal protein and not the tumor (6). This is also supported by in vitro data that showed that different light chains (AL versus LCDD) activate different cellular pathways via the same receptor on mesangial cells (7).…”
Section: Introductionsupporting
confidence: 57%
“…In animal studies, the type of kidney disease is dictated by the monoclonal protein and not the tumor (6). This is also supported by in vitro data that showed that different light chains (AL versus LCDD) activate different cellular pathways via the same receptor on mesangial cells (7).…”
Section: Introductionsupporting
confidence: 57%
“…In vitro studies in the kidneys by Herrera et al show that processing of the Ig by the mesangial cell and subsequent cellular signaling pathways play an important role in the distinction of the deposits. 15,16 AL amyloidosis can manifest as diastolic dysfunction, conduction abnormalities or congestive cardiac failure. Our series show that incidence of CIDD is almost as frequent as AL amyloidosis in patients with plasma cell dyscrasias (31 vs 39%).…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid fibrils are associated with other proteins, including amyloid P, glycosaminoglycans, proteoglycans, fibronectin, and apolipoprotein E (114 -116). In the kidney, the mesangial cells or mesangial macrophages play a central role in amyloidogenesis by endocytosing the precursor proteins into lysosomes, where amyloid fibril formation takes place (84,117). However, not all light chains are amyloidogenic (111,118 -120), and the association between multiple myeloma and amyloid suggests that specific abnormal light-chain sequences underlie fibrillogenesis.…”
Section: Al-amyloidosismentioning
confidence: 99%